1999
DOI: 10.1016/s0022-5223(99)70004-8
|View full text |Cite
|
Sign up to set email alerts
|

Coronary flow reserve early and late after minimally invasive coronary artery bypass grafting in patients with totally occluded left anterior descending coronary artery

Abstract: Our findings suggest that the late improvement in coronary flow reserve is independent of the diameter of the graft and probably reflects an early distal coronary vessel dysfunction, which normalizes with time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…It has been reported that the early postoperative graft flow reserve of the LITA may at times be insufficient because of vasospasm or the effect of cardiopulmonary bypass, 6 so in the present study graft flow was measured immediately before and after repair of stenosis of the LITA graft. Because the myocardial ischemic time was shortened by the use of a continuous coronary blood perfusion system, we believe there was ischemic or reperfusion damage to the myocardium and moreover, the ITA graft was not affected by native LAD flow because there was total occlusion in the proximal native LAD.…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that the early postoperative graft flow reserve of the LITA may at times be insufficient because of vasospasm or the effect of cardiopulmonary bypass, 6 so in the present study graft flow was measured immediately before and after repair of stenosis of the LITA graft. Because the myocardial ischemic time was shortened by the use of a continuous coronary blood perfusion system, we believe there was ischemic or reperfusion damage to the myocardium and moreover, the ITA graft was not affected by native LAD flow because there was total occlusion in the proximal native LAD.…”
Section: Discussionmentioning
confidence: 98%
“…Healthy endothelium modulates the vasomotor tone of the ITA in response to changes in blood flow and to the shear stress caused by the high‐velocity laminar flow, favoring vascular remodeling, and the release of nitric oxide. These changes largely determine subsequent velocities and lower baseline flow values, suggesting adaptation to a lower metabolic demand and resulting in higher values of coronary reserve …”
Section: Discussionmentioning
confidence: 99%
“…The pharmacological stimulation of hyperemia performed 6 months after the CABG enabled the assessment of the functional status of the anastomosed artery based on the analysis of the CFR values …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13, 14 However, the ITA graft can adapt to the higher flow demands of the relevant myocardial area, thus resulting in an increased graft diameter, usually identifiable within 1 month. [15][16][17][18][19] Many studies on the coronary flow reserve of the ITA graft after pharmacological intervention with adenosine, dipyridamole, papaverine, and nitroglycerin, …”
Section: Physiological and Metabolic Effects Of Grafts In Cabgmentioning
confidence: 99%